2022
DOI: 10.1002/jcu.23379
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of gray‐scale ultrasound and shear wave elastography in assessing salivary gland involvement in patients with primary Sjögren's syndrome

Abstract: Purpose To investigate the diagnostic performance of gray‐scale ultrasound (US) and shear wave elastography (SWE) for determining salivary gland involvement primary Sjögren's syndrome (pSS). Methods In this prospective study, the salivary glands of 72 healthy volunteers and 74 participants with pSS were examined by two blinded radiologists with consensus using gray‐scale US and SWE. SWE parameters were compared between groups. The area under the curve (AUC), sensitivity, and specificity of gray‐scale US and SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Shear wave elastography is a promising tool for evaluating tissue stiffness. Recently, the diagnostic value of SWE in the salivary glands of patients with SS has been evaluated in several studies 12,18 . These studies demonstrated that SWE provided excellent diagnostic performance to discriminate between patients with SS and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear wave elastography is a promising tool for evaluating tissue stiffness. Recently, the diagnostic value of SWE in the salivary glands of patients with SS has been evaluated in several studies 12,18 . These studies demonstrated that SWE provided excellent diagnostic performance to discriminate between patients with SS and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The submandibular glands were only scanned in longitudinal sections. The grading system used for diagnosing SS in the present study is presented in Table 1 12 . The grading scores of four major salivary glands were measured, respectively, and the highest score was recorded as the total score for each patient.…”
Section: Methodsmentioning
confidence: 99%